The Influence of Tax Services, Tax Rates and Tax Sanctions on Male and Female MSMe Taxpayer Compliance (Case Study of Individual Taxpayers MSMEs in Tanah Abang Market) - CHARVIANY, Masayu Fenny Amalia; TARMIDI, Deden; FADJARENIE, Agustin (PT Keberlanjutan Strategis Indonesia, 2024)
This research aims to determine whether there are differences in the influence of tax services, tax rates and tax sanctions on male and female MSME taxpayer compliance. The object of this research is individual taxpayers who are MSMEs in Tanah Abang Market. This research uses quantitative methods, samples were taken using random sampling. The total sample used was 230 respondents consisting of 115 male respondents and 115 female respondents. The results of this research shows that Tax Services, Tax Rates, and Tax Sanctions have a significant positive effect on Tax Compliance of Male and Female MSMEs at Tanah Abang Market. Tax sanctions only have a positive effect on the Tax Compliance of Female MSME Actors, while tax sanctions have no effect on the Tax Compliance of Male MSME Actors.